2016
DOI: 10.29311/ndtps.v0i11.581
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a STEM summer undergraduate research internship scheme: student-perceived learning gains

Abstract: The organisation of a STEM-wide summer undergraduate research internship scheme to ensure equal opportunities for all students is reported. Student engagement in the internship programme is much greater in the Biological, Pharmaceutical and Chemical Sciences (142 applications in 2016) than in Engineering and Computing (30 applications in 2016). To evaluate the impact of the scheme, previous interns were surveyed about their perceived learning gains from doing an internship. Twenty three responses were received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Both students and faculty talked about the importance of internships for nontraditional students and career changer as students are navigating their educational and career paths. First, internship provides students the opportunity to implement what they learned in the classroom in real work environments while being supported by college instructors and administrators (Johnson et al., 2017; Williams et al., 2016). In addition, students have hands-on experiences that give them a better sense of if that field is right for them.…”
Section: Discussionmentioning
confidence: 99%
“…Both students and faculty talked about the importance of internships for nontraditional students and career changer as students are navigating their educational and career paths. First, internship provides students the opportunity to implement what they learned in the classroom in real work environments while being supported by college instructors and administrators (Johnson et al., 2017; Williams et al., 2016). In addition, students have hands-on experiences that give them a better sense of if that field is right for them.…”
Section: Discussionmentioning
confidence: 99%
“…Research in other STEM‐based undergraduate summer internship and research programs demonstrates that students identify improvement in critical professional development areas based on these types of experiences. Student self‐identified improvement areas included laboratory techniques, time management, comfort with reading scholarly literature, and independence 42–44 . Unfortunately, the AAPM offers a limited number of SUFP and DREAM opportunities each year, and many available mentors and institutions are not matched with student candidates.…”
Section: Innovationmentioning
confidence: 99%
“…Through exit and follow-up interviews, APT graduates indicated that they perceived that the program gave them an advantage in competitive graduate school admissions processes and provided a solid foundational understanding of basic clinical physics for their graduate studies. [42][43][44] Unfortunately, the AAPM offers a limited number of SUFP and DREAM opportunities each year, and many available mentors and institutions are not matched with student candidates. However, the success of the NMPC internship program has shown that supporting early-career physicists through a summer undergraduate internship program is possible outside of the established AAPM program (and outside of academia), and can result in positive educational experiences for early-career physicists.…”
Section: Apt Programmentioning
confidence: 99%
“…Participating in UGR promotes perceived gains in personal (e.g., understanding people of different backgrounds), practical (e.g., working effectively with others), and general education competency (e.g., solving complex real-world problems) areas, as well as higher satisfaction in their educational experience. These types of gains had been documented in both an apprentice-type research experience and a CURE (Kinner & Lord, 2018;Williams et al, 2016), though both these previous reports focused exclusively on self-reported gains immediately after a single STEM course or summer research experience at a research university. We demonstrate that these gains occur at teaching institutions and potentially persist far beyond the actual UGR experience.…”
Section: The Relationship Between Ugr Participation and Perceived Gains And Overall Satisfactionmentioning
confidence: 99%